The Financial Performance of Islamic Bank in Malaysia: A Comparative Study - Buamoud, Omran F. (1998)
This study analyse the performance of the Islamic bank (Bank Islam Malaysia Berhad) and compares it to benchmark bank (Maybank) in the Malaysian banking sector. The study finds that Bank Islam shows all the characteristics of a newly established bank and hence has an inferior performance compared to a well-established bank. An intervening variable identified during the study is that Bank Islam is operations are constrained by the Islamic law.